Zasady orzekania kary ograniczenia wolności — wybrane zagadnienia - Lachowski, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The paper focuses on the principles of restriction of liberty sentencing as defined in the Criminal Code, especial in view of the significant changes in this respect that occurred in 2015–2016. This most flexible of criminal remedies gives rise to a number of problems as its individual content is constructed. From the moment of the entry into force of the Criminal Code of 6 June 1997 until now the regulations referring to restriction of liberty have evolved considerably. On the one hand, the evolution has involved a gradual transfer of increasingly broad powers to probation officers during sentence enforcement, on the other it has concerned regulations applying to the content and form of this remedy. Generally, restriction of liberty has been gradually imbued with probational elements. Ultimately, it is a sanction the correct application of which requires a lot of attention and gives rise to a range of legal and organisational challenges.
Keywords: zasady skazania; obowiązki okresu próbnego; potrącenia z wynagrodzenia; nieodpłatna praca nadzorowana